Analysis of the status of informed consent in medical research involving human subjects in public hospitals in Shanghai. Issue 7 (6th July 2010) - Jianping, Wang; Li, Lan; Xue, Di; Tang, Zhongjin; Jia, Xieyang; Wu, Rong; Xi, Yiqun; Wang, Tong; Zhou, Ping
Abstract : Objectives: The objectives of the study are to understand the current practice of informed consent in medical research in public hospitals in Shanghai, and to share our views with other countries, especially developing countries. Methods: In the study, 145 consent forms (CFs) of the selected research projects in eight public hospitals with ethics committees in Shanghai were audited, and the principle investigators (PIs) of these research projects and 40 student subjects who had participated in clinical drug tests were surveyed by questionnaires. Results: The CFs of medical researches in public hospitals with ethics committees in Shanghai were generally acceptable. However, there were some defects in the CFs. Although most of the surveyed PIs had correct recognition of informed consent, some processes of informed consent were not in accordance with generally accepted requirements. A large number of the PIs considered the greatest difficulty with informal consent was lack of correct recognition of subjects or legally authorised representatives on medical research. Discussion: Informed consent in medical research should consider the research ethics, the background of potential subjects, the local resources and culture of medical research. In addition, special protection is needed for student subjects in informed consent as well as efforts for building and restoring the public's trust in biomedical research. Conclusion: The informed consent in Shanghai's public hospitals with ethics committees was generally acceptable and the achievement of adequate informed consent is influenced by many factors.